USING THREE TWO ONE TECHNIQUE TO IMPROVE THE BIOGRAPHICAL RECOUNT TEXT READING SKILL OF THE TENTH GRADERS OF SMA N 3 MAGELANG IN THE SCHOOL YEAR 2018/2019 - Titin Nurhayati (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
USING THREE TWO ONE TECHNIQUE TO IMPROVE THE BIOGRAPHICAL RECOUNT TEXT READING SKILL OF THE TENTH GRADERS OF SMA N 3 MAGELANG IN THE SCHOOL YEAR 2018/2019 Titin NurhayatiEnglish Department Faculty Of Education And Teachers’ Training,Tidar Universitytitinnurha1996@gmail.com ABSTRACT                 Reading skill is one of the fundamental skills that has to be mastered by students. It is the ability to understand the written form of the language. The students have to be able comprehend and understand the text. In fact the tenth graders of SMA Negeri 3 Magelang in the school year 2018/2019 have less motivation in learning biographical recount text reading skill and low reading skill of biographical recount text. It is proven by the mean score of biographical recount text reading skill test which is 69 which is still lower than the minimum requirement standard score which is 75. The writer conducted a Classroom Action Research (CAR) in order to know how great is the increase of motivation in learning biographical recount text reading skill and to know how great is the improvement of the biographical recount text reading skill of the tenth graders of SMA N 3 Magelang in the school year 2018/2019 after being taught by using Three Two One Technique.   The subject of the research was X IPA 1 of SMA N 3 Magelang in the school year 2018/2019. The writer uses quantitative data analysis techniques that is test technique and qualitative data analysis technique that is non-test technique (observation, questionnaire, and documentation). The students’ test average scores of biographical recount text reading skill improve after being taught using Three Two One Technique. In the Pre-Cycle the average score 69.32, then improves in Cycle 1 become 89.28, and in Cycle 2 become 93.41. Thus, there is improvement from Pre- Cycle to Cycle 2 that is 24.09 point. The students’ motivation in learning biographical recount text reading skill also increases. It is proven by the results of observation that increase 24.09% from Pre-Cycle to Cycle 2. Then, the results of questionnaire increase 30.66% from Pre-Cycle to Cycle 2.Based on the above results, the writer concludes that the use of Three Two One Technique can increase the students’ motivation in learning biographical recount text reading skill and improve the students’ biographical recount text reading skill. The writer suggests both of the teacher and the students to use Three Two One Technique as an alternative in teaching and learning process of biographical recount text reading skill.Keywords: Reading Skill, Biographical Recount Text, Three Two One Technique